(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
With the emergence of high-end mobile devices and advanced internet technologies (such as 3G and 4G) mobile commerce market has become an attractive and profitable arena for businesses and marketers. The latest buzz in the industry is the transition from wired to wireless networks, i.e. from electronic commerce to mobile commerce or m-commerce. However, mobile commerce is still in its initial stages in terms of its adoption by the end users. The purpose of this study is to identify important factors having significant role in determining mobile commerce adoption intention by consumers and to propose a model utilising the identified factors. For this, a thorough review of literature available on mobile as well as adoption of similar technologies was done. An in-depth study of factors influencing consumers’ decision about mobile commerce can provide useful insights to the concerned marketers for developing suitable marketing strategies.